The Economic Impact of Healthcare Quality - Helso, Anne-Line Koch (IMF Working Papers; Working Paper, 2019)
We study the costs of hospitalizations on patients' earnings and labor supply, using the universe of hospital admissions in Denmark and full-population tax data. We evaluate the quality of treatment based on its ability to mitigate the labor market consequences of a given diagnosis and propose a new measure of hospital quality, the "Adjusted Earning Losses" (AEL). We find a 4 percentage points difference in lost earnings between the best and worst large Danish hospitals, all else equal. We show that AEL contains significant additional information relative to traditional measures and does not suffer from worse selection issues. We also document a large decline in the labor cost of hospitalizations over time, with large variations across diseases. We find that the average post-hospitalization reduction in labor earnings declined by 25 percent (50 percent) on the intensive (extensive) margin between 1998 and 2012.